Studi Kasus dalam Penelitian Kualitatif: Sebuah Tinjauan Sistematis - Nurahma, Gilang Asri; Hendriani, Wiwin (Mediapsi, 2021)
Case studies are often used in qualitative research from a variety of disciplines, such as psychology, sociology, anthropology, political science, and many more. But along with its development, there are several different understandings about what a case study is and how to conduct scientific research using a case study approach appropriately. In fact, the case study approach with the right procedures has flexibility and high accuracy which allows researchers to be able to take a simple to complex phenomenon and develop theories, program designs, interventions. The purpose of this article is to provide a systematic review about case study definitions, types of case studies, and important points that researcher should know to conduct case studies properly. The review data are also summarized systematically in tabulated form.